Тепловые процессы при непрерывном литье стали - Самойлович Ю. А. Юрий Авраамович; Крулевецкий С. А. Семен Аронович; Горяинов В. А. Владимир Александрович; Кабаков З. К. Зотей Константинович (Москва, Металлургия, 1982)
Авт. указаны на обороте тит. л.